Social Justice Character in Early Childhood Legal Education Online: A Literature Review - Muhammad Yusuf; Suci Ramadhona; Iman Jauhari (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines how online learning can be optimized to strengthen social justice character within early legal education contexts. Employing a traditional literature review, the research synthesizes global and Indonesian scholarly works published between 2020 and 2025 that address social justice education, digital pedagogy, and early childhood moral development. The findings indicate that online learning, when intentionally designed, can support the cultivation of fairness, empathy, and civic responsibility among young learners through interactive, story-based, and participatory digital activities. Parental involvement and teacher facilitation emerge as critical factors in translating legal awareness into child-appropriate moral experiences. The review further highlights that value-based digital pedagogy grounded in Pancasila principles and ethical frameworks enhances the integration of cognitive, moral, and social learning. This study implies that early childhood teachers should adopt ethically guided digital strategies, curriculum developers need to embed justice-oriented competencies into online learning designs, and policymakers must ensure equitable digital access and professional support to sustain justice-oriented early legal education.